Analisis Fasa Sistem Mn(1-X)NdxFe2O4 sebagai Kandidat Bahan Penyerap Gelombang Mikro [Phase Analysis of Mn(1-x)NdxFe2O4 System as Candidate of Microwave Absorber Materials] - Yunasfi - Yunasfi; Indri Rachmawati; Mashadi Mashadi; Wisnu Ari Adi; Nurmaya Arofah (Metalurgi, 2018)
Phase analysis of Mn(1-x)NdxFe2O4 system as candidate of microwave absorber materials have been carried out. Mn(1x)NdxFe2O4 (with x = 0.0; 0.1 dan 0.2) system was synthesized by mixing the powder of Fe(NO3)3, Mn(NO3)3 andNd(NO3)3 in mole ratio. The mixture was dissolved with ethyleneglycol, dried at 120C and sintered at 1200C for 3 h.Phase identification with XRD (x-ray diffractometer) shows that multiphase have been formed which is indicated by the appearance of MnFe2O4 and NdFeO3 phase. According to the morphological observation with SEM (scanning electron microscopy), it is known that all of the samples has unhomogeneous structure with particle size is 200-400 nm. The results of microwave absorbing properties measured by VNA (vector network analyzer) shows that the increasing substitution of Nd3+ ion will increased the ability of material to absorb microwave with the highest value of ~93% for the composition of x=0.2 (Mn0.8Nd0.2Fe2O4). AbstrakTelah dilakukan analisis fasa sistem Mn(1-x)NdxFe2O4 sebagai bahan penyerap gelombang mikro hasil sintesis dengan metode sol-gel. Sistem Mn(1-x)NdxFe2O4 (dengan x = 0,0; 0,1 dan 0,2) disintesis dengan mencampurkan serbuk Fe(NO3)3, Mn(NO3)3 dan Nd(NO3)3 sesuai dengan perbandingan molnya. Campuran bahan ini dilarutkan dengan etilen glikol, dikeringkan dengan oven pada suhu 120 °C dan kemudian disinter pada 1200 °C selama 3 jam. Identifikasi fasa menggunakan XRD (X-ray diffractometer) menunjukkan terbentuknya multifasa yang ditandai dengan munculnya fasa MnFe2O3 dan FeNdO3. Pengamatan morfologi dengan SEM menunjukkan terbentuknya struktur yang tidak homogen untuk seluruh sampel dengan ukuran sekitar 200-400 nm. Serapan gelombang mikro yang diukur dengan VNA (Vector Network Analyzer) menunjukkan bahwa substitusi  ion Nd3+ dapat meningkatkan kemampuan material menyerap gelombang mikro, dengan serapan terbesar ~93% oleh komposisi x = 0,2 (Mn0,8Nd0.2Fe2O4).